2018
DOI: 10.20944/preprints201810.0473.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-Specific Labeling of Proteins with Near-IR Dyes

Abstract: Convenient labeling of proteins is important for observing its function under physiological conditions.  In tissues particularly, heptamethine cyanine dyes (Cy-7) are valuable because they absorb in near infrared (NIR) region (750 – 900 nm) where light penetration is maximal.  In this work, we found Cy-7 dyes with a meso-Cl functionality covalently binding to proteins with free Cys residues under physiological conditions (aqueous environments, at near neutral pH, and 37 °C).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Instantaneous red-shift from 780 to 805 nm, followed by a slower blue-shift to 791 nm, can be explained in the following way. Albumin rapidly forms a noncovalent adduct with MHI-148, 1-Cl, followed by slower transformation into a Cys 34 -bound covalent adduct, consistent with the data we reported previously, 34,35 and the work of Canovas et al 37 Support for this assertion comes from the corresponding experiment with the meso-blocked dye 1-Ph (Figure 3). For 1-Ph, Figure 3a shows addition of albumin led to instantaneous formation to a new UV spectrum with a red-shifted absorption maximum, which is invariant over 5 h, the time span of the experiment.…”
Section: Effects Of Albumin Outweigh Those Of Bsp In Sfmsupporting
confidence: 89%
See 4 more Smart Citations
“…Instantaneous red-shift from 780 to 805 nm, followed by a slower blue-shift to 791 nm, can be explained in the following way. Albumin rapidly forms a noncovalent adduct with MHI-148, 1-Cl, followed by slower transformation into a Cys 34 -bound covalent adduct, consistent with the data we reported previously, 34,35 and the work of Canovas et al 37 Support for this assertion comes from the corresponding experiment with the meso-blocked dye 1-Ph (Figure 3). For 1-Ph, Figure 3a shows addition of albumin led to instantaneous formation to a new UV spectrum with a red-shifted absorption maximum, which is invariant over 5 h, the time span of the experiment.…”
Section: Effects Of Albumin Outweigh Those Of Bsp In Sfmsupporting
confidence: 89%
“…Covalent bond formation of dyes 1-Cl−4-Cl was supported via HPLC analyses, and previous work by our group 34,35 and by Conovas et al 37 The current study (Figure S11) showed that relative rates for the formation of covalent adducts were (at 37 °C with 2 equiv of HSA): 4-Cl (IR780; t 1/2 2 min) ≫ 1-Cl (6 h) > 3-Cl (24 h) > 2-Cl (72 h), and formation of an adduct from 5-Cl only proceeded to ~30% after 72 h under these conditions (data not shown). In vivo we expect the dyes to convert to covalent adducts more rapidly due to the high concentration of albumin in serum.…”
Section: Effects Of Albumin Outweigh Those Of Bsp In Sfmmentioning
confidence: 80%
See 3 more Smart Citations